Subdesenvolvimento, imperialismo, educação, ciências e tecnologia no Brasil: a subordinação reiterada - Mello, Noval Benaion (2009)
The amount of knowledge accumulated by a nation directly reflects on many dimensions of its material wealth. No developed country has arrived at a leading position within the world order of material and intellectual production without focusing on its technological, scientific and intellectual development. In the Brazilian case, the centrality of that theme within government discourses and agenda has not been matched by its actions in practice. Based on that premise, the present study seeks to understand the reasons that determine the kind of formation of Brazilian society, as well as how those very reasons influence the slowing down or the stagnation of the economy, during the last two decades of the last century. It investigates how macroeconomic and social issues, such as debts towards external agents, international commerce and income distribution, impinge on the quality of education, science and technology, as well as on the type of culture that mirrors dominant imperialist relations in the country. I seek to understand the underdevelopment condition characterized by high tolls of unemployment and illiteracy, as well as by all the other factors that take part in the social and economic stagnation, as a by-product of deliberate political actions of countries that determine domineering and dependency relationships within the scope of the integration between centre and periphery. At the national level, the study focuses on the visibility of issues that contribute to the consolidation of the current political, economical, social and cultural position of Brazil as a losing, subordinate and underdeveloped country. By investigating the economic and social constitution of the country, it argues that many of the traces inherent to the colonial period still linger on in the current era. The research methodology intends to offer an alternative perspective relative to a predominant determinist, mechanicist and reductionist one, that underlie most research methodologies, particularly in social sciences. National economic scenario has shown that the country has had a negative growth in the last decades, particularly due to the dominant character of its upper classes and to the passive acceptance of its dominated classes. Government prejudiced assumptions related to the integrated nature of education, science and technology and of the kind of necessary incentives to national production destined to the satisfaction of social needs have strongly affected the fragile research system in the country. The progressive destruction of the system of basic research turned towards mass consumption illustrates the contempt that governments have had towards the public welfare.